Influence of Frictional Melt on the Seismic Cycle: Insights From Experiments on Rock Analog Material. Issue 1 (28th December 2022) - Conrad, E. M.; Tisato, N.; Carpenter, B. M.; Di Toro, G.
Abstract: The formation of frictional melt likely impacts the coseismic and, when solidified (pseudotachylyte), the interseismic strength of faults. Here we investigate these effects through experiments using a new energy‐controlled rotary shear machine (ECoR) on simulated faults made of a transparent rock analog material (polymethyl‐methacrylate). As in nature, ECoR allows (a) elastic strain energy to accumulate at different loading rates and (b) the spontaneous nucleation of slip events. ECoR is equipped with a high‐speed camera, thermocouples, and transducers to monitor the surface, temperature, and acoustic emissions (AEs), respectively. We perform experiments at normal stresses of ∼3.5 MPa across loading rates from 0.15 MPa/s, phase A, to 2.5 MPa/s, phases B‐C‐D. In phase A, the temperature remains constant, and slip events occur without visible melting every 3.3–6.4 s with 0.5–0.7 MPa stress drops and 3–7 mm displacements. In phases B‐C, slip events occur in the presence of melts every 0.5–0.9 s, and the bulk temperature increases progressively. Melt solidification increases static friction yielding slip events with stress drops up to 5 MPa and displacements up to 3 cm. Samples produce high‐frequency AEs during slip acceleration and deceleration. Once the bulk temperature reaches ∼110°C, a "final" and silent long displacement event occurs in the presence of melts (phase D). Experimental observations suggest that melt formation modulates the coseismic (flash melting, melt lubrication, and viscous braking) and interseismic (welding) stages. Furthermore, AEs associated with coseismic fault weakening and strengthening may have their natural equivalent and could be observed in seismograms through near‐fault instrumentation. Plain Language Summary: During earthquakes, rocks slide against each other result in frictional heat. In some cases, enough heat is generated that rocks melt, influencing earthquake behavior. We investigate this behavior with experiments using a newly devised laboratory apparatus on a rock‐analog material, polymethyl‐methacrylate glass (commercial name, Plexiglas®). The apparatus reproduces the natural earthquake cycle by compressing two cylinders (top and bottom sample) in the vertical direction, then gradually loads a spring, applying a horizontal shear force where the two samples meet. Slip between the samples occurs when the force from the spring overcomes the ability of the material to resist shearing. This process mimics earthquakes along faults at depth, generating heat and melts. We find that during slip, such melts initially lubricate the fault, then cool, thicken, and increase viscosity to resist slip. Moreover, the solidification of melts increases the fault strength leading to larger successive earthquakes. We used acoustic sensors to monitor the sound and vibrational waves emitted from slip events. These recordings reveal the occurrence and timing of the processes happening during faulting. As monitoring technology improves, the waves' characteristic of these processes may also become evident in seismograms of natural earthquakes and help us understand how earthquakes work. Key Points: We use a newly conceived experimental machine on polymethyl methacrylate to investigate the seismic cycle in the presence of melts Energy flux pulses from the machine to the fault yield fault weakening (flash melting + lubrication) and strengthening (viscous braking) Distinct acoustic emission signals correlate with the activation of coseismic fault weakening/strengthening mechanisms